An Energy-Aware Middleware for Integrating Wireless Sensor Networks and the Internet - Jeisa Domingues; Antonio Damaso; Rilter Nascimento; Nelson Rosa (International Journal of Distributed Sensor Networks)
Wireless sensor networks (WSNs) have great potential for many distributed applications in different scenarios. As they grow in popularity and importance, it becomes increasingly desirable and necessary to share their data over the Internet. This paper presents an energy-aware middleware that focuses on integrating the Internet and WSNs at service level by providing transparency of access, location, and technology. In particular, it describes and evaluates the implemented strategies to reduce the energy consumption, which are essential for prolonging the WSN lifetime.